2017
DOI: 10.1177/0954407017732860
|View full text |Cite
|
Sign up to set email alerts
|

Super twisting controller-based unified FDI and FTC scheme for air path of diesel engine using the certainty equivalence principle

Abstract: This paper proposes a combination of higher order sliding mode and adaptive control for unified fault detection and isolation and fault tolerant control (FTC) of the air path of a diesel engine. Current diesel engines are equipped with features such as variable geometry turbochargers (VGT) and exhaust gas recirculation (EGR) for exhaust emission control. Since EGR and VGT systems are present in the exhaust channel, they are strongly coupled and are prone to both structured as well as unstructured faults. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As the complexity of the system increases, the design process of the controller becomes more difficult. In [ 39 ], a certainty equivalence-based super-twisting algorithm (CESTA) is implemented on a diesel engine for the diagnosis of match uncertainties and later it is counteracted. In [ 40 ], the certainty equivalence-based integral sliding mode control (CEISMC) technique is being utilized to diagnose and mitigate the actuator fault for the diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…As the complexity of the system increases, the design process of the controller becomes more difficult. In [ 39 ], a certainty equivalence-based super-twisting algorithm (CESTA) is implemented on a diesel engine for the diagnosis of match uncertainties and later it is counteracted. In [ 40 ], the certainty equivalence-based integral sliding mode control (CEISMC) technique is being utilized to diagnose and mitigate the actuator fault for the diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…19 For a single-tank system with system faults and process disturbances, a fuzzy logic-based passive fault-tolerant control method was proposed in Patel and Shah. 20 In Murtaza et al, 21 a super-twisting control-based unified FDI and FTC system for the air path of diesel engines is reported. Kalman Filters (KFs) were also used in the FDI architecture of gas turbines for faulty sensor estimation 22,23 consisting of both hardware and analytical redundancies.…”
Section: Introductionmentioning
confidence: 99%
“…In Patel and Shah, 33 PFTCS has been reported using fuzzy logic and proportional–integral (PI) controller for a single tank level system under system faults and process disturbances. In Murtaza et al, 34 super twisting control-based unified FDI and FTC scheme is reported for air path of diesel engines. In Pourbabaee et al, 35 HFTCS is implemented using multiple KFs in the FDI design for gas turbine engines.…”
Section: Introductionmentioning
confidence: 99%